The Effect of Massage for Babies Aged 0-6 Months on Sleep Quality - Wardani, Ika Kania Fatdo (Universitas Islam Lamongan, 2023)
Scientifically, massage provides a stimulus to hormones in the body, a substance that regulates functions such as appetite, sleep, memory and learning, temperature regulators, mood, behavior, vascular function, muscle contraction, endocrine system regulators (regulators of metabolism, growth, and puberty) and depression. The research method is carried out using quantitative research methods with a Quasi-Experimental approach using Wilcoxon statistical tests (Abnormally Distributed). The population in this study was all mothers who had babies. The sample in this study was mothers who had babies aged 0-6 months in Bantarjaya Village using the total sampling technique, the total sample number of 40 people. Data collection with questionnaires. Data analysis is a univariate, bivariate and multivariate analysis. The output of this study is an article published in an Accredited National Journal and the production of HKi in the form of a baby massage pocket book. The results showed that out of 40 babies based on the quality of baby sleep during pretest, the most in babies whose sleep quality was not good, which was 60.0% compared to the quality of good sleep of babies. After a baby massage (post test), the quality of a good baby's sleep increased to 31 people (77.5%). Meanwhile, the quality of sleep of babies who are not good is reduced to 9 people (22.5%). The results of statistical tests are known to Asymp. Sig is worth 0.000 (P < 0.05), then it can be concluded that the hypothesis is accepted. This means that there is a difference between the Pretest and Posttest results, so it can also be concluded that there is an influence on the implementation of baby massage by improving sleep quality in babies aged 0-6 months in Bantarjaya Village, Pebayuran District, Bekasi Regency in 2022. The dominant characteristic variable is Education. There needs to be a role from health workers and the Health office to increase the knowledge and motivation of mothers in doing baby massage, the aim is to improve the quality of baby sleep and prepare for baby growth and development through community empowerment such as cadres, community leaders and religious leaders.Â